Pandemic and student mental health: mental health symptoms among university students and young adults after the first cycle of lockdown in the UK. Issue 4 (26th July 2022) - Tang, Nicole K. Y.; McEnery, Katharine A. M.; Chandler, Laura; Toro, Carla; Walasek, Lukasz; Friend, Hannah; Gu, Sai; Singh, Swaran P.; Meyer, Caroline
Abstract : Background: Early COVID-19 research suggests a detrimental impact of the initial lockdown on young people's mental health. Aims: We investigated mental health among university students and young adults after the first UK lockdown and changes in symptoms over 6 months. Method: In total, 895 university students and 547 young adults not in higher education completed an online survey at T1 (July–September 2020). A subset of 201 university students also completed a 6 month follow-up survey at T2 (January–March 2021). Anxiety, depression, insomnia, substance misuse and suicide risk were assessed. Results: At T1, approximately 40%, 25% and 33% of the participants reported moderate to severe anxiety and depression and substance misuse risk, clinically significant insomnia and suicidal risk. In participants reassessed at T2, reductions were observed in anxiety and depression but not in insomnia, substance misuse or suicidality. Student and non-student participants reported similar levels of mental health symptoms. Student status was not a significant marker of mental health symptoms, except for lower substance misuse risk. Cross-sectionally, greater symptoms across measures were consistently associated with younger age, pre-existing mental health conditions, being a carer, worse financial status, increased sleep irregularity and difficulty since lockdown. Longitudinally, T2 symptoms were consistently associated with worse financial status and increased difficulty sleeping at T1. However, these associations were attenuated when baseline mental health symptoms were adjusted for in the models. Conclusions: Mental health symptoms were prevalent in a large proportion of young people after the first UK lockdown. Risk factors identified may help characterise high-risk groups for enhanced support and inform interventions.